The influence of Ce content and preparation temperature on the microstructure and oxidation behavior of Ce–modified Cr coating on open–cell NiCrFe alloy foam. (July 2016) - Pang, Q.; Hu, Z.L.; Sun, D.L.
Abstract: The Ce/Cr coating was deposited onto the surface of the open–cell NiCrFe alloy foam by the pack cementation. The effects of process parameters (Ce content and preparation temperature) on the microstructure and oxidation behavior of the Ce/Cr coatings were systematically investigated. Isothermal oxidation tests of Ce/Cr coatings with various Ce contents were performed at 1000 °C for 120 h, which were also compared with those of the substrate and Cr coating. Scanning electron microscopy and energy dispersive analysis (SEM/EDS) were used to investigate the microstructure and chemical composition of the Ce/Cr coatings before and after oxidation, respectively. The results show that the addition of CeO2 powders in the packs distinctly influences the coating thickness, the contents of Cr, and the density of cavities in the coatings. In addition, the oxidation resistance of the Ce/Cr coatings is improved with the adding of Ce element. This is due to that these large Ce atoms give rise to a "site-blocking" effect for the outward transport of the cations and the inward Cr diffusion. As a result, Cr2 O3 content is increased sharply in the oxide layer. Especially the 2 wt% Ce/Cr coating exhibits the best oxidation resistance performance. Highlights: CeCr coating was successfully synthesized on NiCrFe alloy foam by pack cementation. Microstructure of CeCr coating was improved by Ce addition and processing temperature. Addition of Ce to Cr coating improved the oxidation resistance. Adding Ce to Cr coating can accelerate the deposition by the gas group structures of Ce.